Evaluation of Quality and Acceptability of Snack (Kokoro) Produced From Synthetic Provitamin A Maize (Zea mays) Genotypes - Akinsola, Omololami Tolulope; Alamu, Emmanuel Oladeji; Otegbayo, Bolanle Omolara; Menkir, Abebe; Maziya-Dixon, Busie (Frontiers in Sustainable Food Systems, 2020)
Kokoro, an indigenous white maize-based snack consumed in south-western Nigeria, is deficient in provitamin A carotenoid. This study evaluated the chemical composition, carotenoid retention, and acceptability of Kokoro from three biofortified IITA provitamin A (PVA) maize genotypes and one yellow maize variety (control). The chemical composition of PVA Kokoro, yellow maize Kokoro, and commercially purchased Kokoro was moisture content 5.94–8.72%, crude protein 6.72–7.79%, crude fiber 1.89–2.55%, crude fat 23.21–32.11%, ash 1.13–2.24%, and carbohydrate 51.06–56.71%. Kokoro 4 (yellow maize) was the most acceptable, while among the PVA Kokoro, Kokoro 2 was acceptable. Before processing, the carotenoids lutein, zeaxanthin, total β-carotene, and PVA in Maize 1 to Maize 4 ranged from 10.38 to 12.87µg/g, 6.03‒10.97µg/g, 3.83‒6.18µg/g, and 5.96‒8.43µg/g, while after processing to Kokoro, total β-carotene ranged from 1.47 to 3.10µg/g and total PVA content 2.43‒4.00µg/g. The carotenoid retention in Kokoro 1 to Kokoro 4 ranged from zeaxanthin 5.89–8.39%; lutein 2.74–4.45%; total β–carotene 38.24–66.14% and total PVA 37.98–67.05%. After processing, Kokoro1 had the highest PVA value and carotenoid retention. The result shows that PVA retention of Kokoro was genotype-dependent, and genotype PVASYNHGBC0 (Provitamin A maize HGA cycle zero) used in the production of Kokoro 1 retained the highest carotenoid content. Also, among the maize samples used Kokoro 1 (for all the servings size (100g and 150g) in all age groups had the highest percentage contribution of vitamin A to recommended daily allowance. However, further improvement on the carotenoid content of maize genotypes is needed to enable the production of nutritious Kokoro with higher vitamin A percentage contribution and retinol equivalent.